2013
DOI: 10.2106/jbjs.l.00709
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Hip Abductor Tendon Tears

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 28 publications
2
129
1
1
Order By: Relevance
“…Trans-osseous repair using nonabsorbable sutures to reattach the abductor mechanism to the greater trochanter seems to be the favoured option [3,4,[14][15][16]. Results of these procedures are unpredictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans-osseous repair using nonabsorbable sutures to reattach the abductor mechanism to the greater trochanter seems to be the favoured option [3,4,[14][15][16]. Results of these procedures are unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients still walked with a limp and two patients had a positive Trendelenburg test. Davies et al [16] described 24 patients (22 women, two men) with a mean age of 67 years with trans-osseous sutures or suture anchor repair of the glutei. In their series they reported that all but one patient had improvement in hip pain and muscle strength at a minimum two-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for outcomes of surgical repair of gluteal tendon tears is limited to case reports, which provide only weak evidence. Patients who have failed conservative rehabilitation, have significant abductor muscle weakness and have a muscle tear identified on MRI are generally reported to do well in the 1-to 2-year follow-up period following surgery [15,[81][82][83][84][85]. But, in the absence of a control group, it is unclear whether this is better than the natural course.…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…10,11 Traditionally, this was performed through an open approach because this allowed visualization of the footprint, preparation of bone surfaces, and fixation of tendon to bone. [12][13][14] However, with advancements in endoscopic instruments and techniques, there has been a recent increase in the prevalence of endoscopic repairs. [15][16][17][18] The aim of this systematic review was to compare the outcomes of open versus endoscopic gluteal repairs and provide an algorithm regarding the indications and benefits for each approach.…”
mentioning
confidence: 99%